Drainage principles and applications : (International Institute for Land Reclamation and Improvement (ILRI), 2006)
The main characteristic of this series is that the books are "practical" in the sense that they can be used in the day-to-day work of those professionals (mostly engineers) who are involved in irrigation and drainage.